Comparison Between Proprioceptive Neuromuscular Facilitation and Mckenzie Method in Lumbar Range of Motion on Non-Specific Low Back Pain - Panjaitan, Lucky Anggiat; Che Hon, Wan Hazmy; Baait, Siti Nur; Mawaddah, Nurul (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
One of activity that contributed to non-specific low back pain (LBP) is prolonged sitting. Therapeutic exercise that commonly used for management of non-specific LBP is McKenzie method while the Proprioceptive Neuromuscular Facilitation (PNF) exercise was rarely used for non-specific LBP. The purpose of the study is to find the effect of PNF and McKenzie method in lumbar range of motion (ROM) on non-specific LBP. A quasi-experimental study involving 36 subjects (students and staffs) from the university population. The subjects were assigned to three treatment groups: PNF group, McKenzie group and control group (hot pack and educational home exercise sheet) which underwent 12 treatment sessions distributed over three times in a week for four weeks duration. Subjects were measured on lumbar flexion and extension ROM by modified schober method. Measurement was performed at three points: pre-test, mid-test and post-test. The within-between groups repeated measures ANOVA were used to analyse the effectiveness of PNF and McKenzie treatments based on the measurement time. This study showed each treatment has significant improvement lumbar flexion ROM (p<0.05) and extension ROM (p<0.05) after 4 weeks. However, there is no significant difference between PNF and McKenzie method in increasing lumbar flexion ROM (p=0.100) and extension ROM (p=0.127) after 4 weeks. The study findings showed that the PNF exercise and McKenzie method has no difference in improving of lumbar ROM on non-specific LBP subjects.